The Implications of the Trinity on One's Relationship With God and Fellow Human Beings in St. Andrew’s Cathedral, Muhabura Diocese (2010-2025) - Aggrey Mugarura (Uganda Christian University, 2025)
This dissertation investigates the theological implications of the doctrine of the Trinity on the personal faith and communal relationships of congregants at St. Andrew’s Cathedral, Muhabura Diocese, from 2010 to 2025. The study is situated within a context of historical church conflict, making the exploration of a relational God particularly relevant for healing and unity. The research employed a qualitative methodology, utilizing surveys, interviews, and theological literature review to gather data from a diverse demographic within the cathedral community. The central findings reveal that a robust understanding of the Trinity as one God in three persons—Father, Son, and Holy Spirit—profoundly enhances believers' relationships with God. This understanding fosters a deeper sense of divine closeness, security in faith, and a comprehensive prayer life directed to all three persons of the Godhead. Furthermore, the study demonstrates that the Trinity provides an essential theological model for human relationships. The perfect unity, mutual love, and self-giving communion within the Godhead serve as a paradigm for Christian community. Believers reported that this doctrine directly inspires them to pursue unity, practice radical forgiveness, extend kindness, and engage in collaborative service within their church and wider community. The relational nature of God, therefore, translates into practical ethics, shaping a communal ethos that values diversity within unity, mirroring the divine perichoresis. The dissertation concludes that the doctrine of the Trinity is not an abstract theological concept but a vital framework for transformative spiritual and social practice. It is foundational for nurturing a vibrant, reconciled, and loving community, especially in a post-conflict context. Recommendations include implementing targeted educational programs to deepen Trinitarian understanding and promoting community initiatives that embody the relational principles of unity and love found in the Triune God.
UNDERGRADUATE RESEARCH